1 - Ajustement structurel et développement en Afrique : L’expérience des années 1980: by Armand Gilbert Noula - Armand Gilbert Noula (Africa Development, 1995)
The colonial style of economic development implemented in Africa produced structural economic imbalances which were intensified by post- independence policies. The SAPs that were supposed to hold them in check were, unfortunately, unable to contain them In addition, neither did the SAPs restore the balance and solvency of States, nor did they contribute to initiating development. As a matter of fact they generated adverse social effects and weakened the States and their internal capacities. A re-orientation of the SAPs toward the creation of favourable conditions for a sustainable development calls for a change of approach.